Microbiome and Its Dysbiosis in Inborn Errors of Immunity - Madhubala Sharma; Manpreet Dhaliwal; Rahul Tyagi; Taru Goyal; Saniya Sharma; Amit Rawat (Pathogens, 2023)
Inborn errors of immunity (IEI) can present with infections, autoimmunity, lymphoproliferation, granulomas, and malignancy. IEIs are due to genetic abnormalities that disrupt normal host-immune response or immune regulation. The microbiome appears essential for maintaining host immunity, especially in patients with a defective immune system. Altered gut microbiota in patients with IEI can lead to clinical symptoms. Microbial dysbiosis is the consequence of an increase in pro-inflammatory bacteria or a reduction in anti-inflammatory bacteria. However, functional and compositional differences in microbiota are also involved. Dysbiosis and a reduced alpha-diversity are well documented, particularly in conditions like common variable immunodeficiency. Deranged microbiota is also seen in Wiskott–Aldrich syndrome, severe combined immunodeficiency, chronic granulomatous disease, selective immunoglobulin-A deficiency, Hyper IgE syndrome (HIGES), X-linked lymphoproliferative disease-2, immunodysregulation, polyendocrinopathy, enteropathy, x-linked syndrome, and defects of IL10 signalling. Distinct gastrointestinal, respiratory, and cutaneous symptoms linked to dysbiosis are seen in several IEIs, emphasizing the importance of microbiome identification. In this study, we discuss the processes that maintain immunological homeostasis between commensals and the host and the disruptions thereof in patients with IEIs. As the connection between microbiota, host immunity, and infectious illnesses is better understood, microbiota manipulation as a treatment strategy or infection prevention method would be more readily employed. Therefore, optimal prebiotics, probiotics, postbiotics, and fecal microbial transplantation can be promising strategies to restore the microbiota and decrease disease pathology in patients with IEIs.